Using the graph below, calculate the average rate of change for f(x) from x = 0 to x = 2.
![Using the graph below calculate the average rate of change for fx from x 0 to x 2 class=](https://us-static.z-dn.net/files/d06/f0b0280afccf060bb0116c7d4575aa0d.png)
we know that
Using the graph
For [tex]x=0[/tex] -----> [tex]f(0)=-2[/tex]
For [tex]x=2[/tex] -----> [tex]f(2)=6[/tex]
the average rate of change is equal to
[tex]\frac{f(2)-f(0)}{2-0} =\frac{6-(-2)}{2}=4[/tex]
therefore
the answer is
the average rate of change is [tex]4[/tex]